2018
DOI: 10.3389/fpls.2018.01616
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cytogenetic Characterization of Six Wheat-Aegilops markgrafii Disomic Addition Lines and Their Resistance to Rusts and Powdery Mildew

Abstract: Aegilops markgrafii (Greuter) Hammer is an important source of genes for resistance to abiotic stresses and diseases in wheat (Triticum aestivum L.). A series of six wheat ‘Alcedo’-Ae. markgrafii chromosome disomic addition lines, designated as AI(B), AII(C), AIII(D), AV(E), AIV(F), and AVIII(G) carrying the Ae. markgrafii chromosomes B, C, D, E, F, and G, respectively, were tested with SSR markers to establish homoeologous relationships to wheat and identify markers useful in chromosome engineering. The addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
(70 reference statements)
2
15
0
Order By: Relevance
“…Chromosome G (4C) had KASP markers assigned from homoeologous groups 4/2/3/7. This partially matched the results by Danilova et al (2017) and Niu et al (2018) who found that chromosome G had markers from homoeologous groups 4/2/3. Our studies found one marker from homoeologous group 7 assigned to chromosome 4C of Ae.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Chromosome G (4C) had KASP markers assigned from homoeologous groups 4/2/3/7. This partially matched the results by Danilova et al (2017) and Niu et al (2018) who found that chromosome G had markers from homoeologous groups 4/2/3. Our studies found one marker from homoeologous group 7 assigned to chromosome 4C of Ae.…”
Section: Discussionsupporting
confidence: 88%
“…caudata chromosome. An addition line for chromosome A is absent from this set, but reports have suggested it to be homoeologous to group 1 of wheat (Danilova et al, 2017; Friebe et al, 1992; Niu et al, 2018). Thus, the 26 markers that did not detect Ae.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations